Comparison of results analyzed by Chinese and European laboratories for FOREGS geochemical baselines mapping samples - Wensheng Yao (Geoscience Frontiers, 2011)
Geochemical subsoil data obtained from China and European laboratories have been compared in this study. 787 C horizon subsoil samples from FOREGS (Forum of European Geological Surveys) geochemical baselines mapping project were sent to China’s IGGE (Institute of Geophysical and Geochemical Exploration) laboratory and composited to 190 samples according to the 160 km × 160 km GNT (Global Terrestrial Network) cells. In addition to the FOREGS elemental analysis package, Au, Pt, Pd, B, Ge, Br, Cl, Se, N, Li and F were also analyzed by using the IGGE’s 76 element analytical scheme. Geochemical data statistics, scatter plotting, and geochemical map compilation techniques have been employed to investigate differences between FOREGS and IGGE analytical results. The results of two datasets, the IGGE’s analysis data for composited samples, and the FOREGS average data of samples in each GNT cell, agree extremely well for about 23 elements, viz: SiO2, Sr, Al2O3, Zr, Ba, Fe2O3, Ti, Rb, Mn, Gd, CaO, Ga, MgO, P, Pb, Na2O, Y, Th, As, U Sc, Cr, and Co. There are slight differences between-laboratory biases shown as proportional errors between the datasets for Ni, K2O, Tb, Tl, Cu, S, Sm, La, Ce, Pr, Nd, Eu, Ho, Er, Tm, Yb, Lu, Ta, Nb, Hf, and Dy. For Cd, Cs, Be, Sb, In, Mo, I, Sn, and Te, the correlation of the two datasets and the similarity of the geochemical maps are fairly good, but obvious biases exist between the two datasets at values near detection limits. Sensitivities of FOREGS analytical methods for W, Bi, Sn, Te, Be, and I are insufficient to produce reportable values in at least 80% of the samples. Although the detection limits of Ag for both FOREGS and IGGE are sufficient to provide reportable values, a large bias was found between the two datasets. This study demonstrates that consistent analytical data for certain elements of global geochemical mapping samples can be achieved by different qualified laboratories, such as China’s IGGE laboratory and some European laboratories. For some elements, such as Ag, further research on the selection of the proper analytical methods and on the development of quality control methods should be undertaken — with final recommendations adhered to by all participants of the global geochemical mapping program.